Time Series Analysis of Congestive Heart Failure Discharges in Florida (USA) Post Tropical Cyclones. Issue 2 (24th April 2023) - Kim, Inkyu; Locascio, Joseph J.; Sarin, Ritu; Hart, Alexander; Ciottone, Gregory R.
Abstract: Objectives: The aim of this study was to analyze congestive heart failure (CHF) discharges in Florida (USA) post tropical cyclones from 2007 through 2017. Methods: This was a retrospective longitudinal time series analysis of hospital CHF quarterly discharges across Florida using the Healthcare Cost and Utilization Project (HCUP) database. The autoregressive integrated moving average (ARIMA) model was used with correlated seasonal regressor variables such as cyclone frequency, maximum cyclone wind speed, average temperature, and reports of influenza-like illness (ILI). Results: A total of 3, 372, 993 patients were identified, with average age in each quarter ranging 72.2 to 73.9 years and overall mortality ranging 4.3% to 6.4%. The CHF discharges within each year peaked from October through December and nadired from April through June with an increasing overall time trend. Significant correlation was found between CHF discharge and the average temperature (P <.001), with approximately 331.8 less CHF discharges (SE = 91.7) per degree of increase in temperature. However, no significant correlation was found between CHF discharges and frequency of cyclones, the maximum wind speed, and reported ILI. Conclusions: This study suggests that with the current methods and the HCUP dataset, there is no significant increase in overall CHF discharges in Florida as a result of recent previous cyclone occurrences.